Improving students' English Vocabulary Mastery through the application of Minecraft Video Game-based Learning Media - Royyan, Faris Mohammad; Priyatmojo, Arif Suryo (Borobudur Educational Review, 2025)
Vocabulary mastery is the main foundation in English language learning, but junior high school (SMP) students often face motivational constraints and boredom with conventional teaching methods. In response to this challenge, this study examines the effectiveness of using Minecraft video games as an innovative learning medium. The main purpose of this study is to quantitatively measure the influence of the use of Minecraft on the improvement of English vocabulary mastery in grade VIII students of SMP Negeri 2 Temanggung for the 2023/2024 school year. This study adopts a quasi-experimental method with a pre-test post-test control group design. The research sample consisted of 61 grade VIII students divided into two groups: the experimental group that received Minecraft-based learning treatment (n=31), and the control group that followed conventional learning (n=30). Data collection instruments include vocabulary mastery tests (before and after treatment), observation sheets to measure student involvement, and questionnaires to determine students' responses to learning media. The results showed a significant difference in performance between the two groups. The experimental group that used Minecraft showed a much higher increase in the average post-test score compared to the control group. In addition to improving cognitive learning outcomes, observational data and questionnaires also revealed that students in the experimental group showed superior enthusiasm, participation, and motivation to learn. Students view Minecraft as a fun, interactive, and effective learning tool in reducing the perception that learning vocabulary is difficult. Thus, the application of Minecraft as a learning medium has a significant and effective positive influence on improving the English vocabulary mastery of junior high school students.